The management of moral hazard through the implementation of a Moral Compliance Model (MCM) - Leire San-Jose; Jose Felix Gonzalo; Maite Ruíz-Roque\~ni (European Research on Management and Business Economics (ERMBE), 2022)
Moral hazard in an organization occurs when people make decisions and take a high risk for their own benefit, given that they would not have to bear all the negative ensuing consequences should they occur. This risk transferred to third parties is generally due to the catalysts that foster this risk, namely, information asymmetries, power, trust and temporality. The contribution of our research lies in the inclusion of moral decisions in project management, thus demonstrating the feasibility of a Moral Compliance Model (MCM). This model is a complement to legal compliance and allows a connection to be established between Risk Management, Governance & Compliance. In 2019, experimental action research, combined with a Plan-Do-Check-Action applied to a company, were used to perform the analysis. The findings show that implementing this moral model in organisations is possible. However, what moral hazard is needs to be shown, along with identifying moral hazard situations and planning how to introduce moral hazard into the risk management model in order to reduce its negative effect or, ideally, eliminate it. We provide an overview of risks, including those around moral dilemma decisions; moral hazard situations that will expand compliance to integrated compliance in which not only legal, but also moral aspects are identified and assessed. Incorporating ethical dilemmas in strategic decisions is a robust advance towards responsible businesses.
Keywords: M140; 650; Compliance; Corporate governance; Corporate management; Moral entrepreneurship; Moral hazard; Risk management; Stakeholder